THE IMPACT OF MATERNAL CARDIAC DISEASES ON FETAL OUTCOMES: A RETROSPECTIVE COHORT STUDY - SIDDIQUI, ES; ABBASI , M; KHOSA, MS; MOHSIN, R; JABEEN , N; SIDDIQUE, U; KHATOON , F (Biological and Clinical Sciences Research Journal, 2023)
This retrospective cohort study aimed to investigate the impact of maternal cardiac diseases on fetal outcomes at the Liaquat University of Medical & Health Sciences (LUMHS). The study was conducted over one year, from December 2018 to December 2019, and involved a sample size of 120 participants. The study utilized medical records of pregnant women with cardiac diseases who delivered at LUMHS over the past 5 years. The data collected included maternal demographic and medical history, fetal and neonatal outcomes, and other relevant medical information. Descriptive statistics were used to analyze the data and determine the prevalence of maternal cardiac diseases and their impact on fetal outcomes. Logistic regression analysis was used to identify risk factors associated with adverse fetal outcomes, such as preterm birth, low birth weight, stillbirth, and congenital anomalies. The results showed that 20% of pregnant women had cardiac disease, with rheumatic heart disease being the most common. Women with cardiac diseases were found to be at higher risk for adverse fetal outcomes, including preterm birth, low birth weight, stillbirth, and congenital anomalies. Logistic regression analysis revealed that maternal age, parity, and type of cardiac disease were significant predictors of adverse fetal outcomes. These findings emphasize the importance of early identification and managing maternal cardiac diseases to prevent adverse fetal outcomes. The study contributes to growing maternal and fetal health research, particularly in high-risk populations such as pregnant women with cardiac diseases. It underscores the need for multidisciplinary management involving obstetricians, cardiologists, and neonatologists to optimize maternal and fetal outcomes in this population.